Patient-tailored antithrombotic therapy following percutaneous coronary intervention. (29th January 2021) - van der Sangen, Niels M R; Rozemeijer, Rik; Chan Pin Yin, Dean R P P; Valgimigli, Marco; Windecker, Stephan; James, Stefan K; Buccheri, Sergio; ten Berg, Jurriën M; Henriques, José P S; Voskuil, Michiel; Kikkert, Wouter J
Abstract: Dual antiplatelet therapy has long been the standard of care in preventing coronary and cerebrovascular thrombotic events in patients with chronic coronary syndrome and acute coronary syndrome undergoing percutaneous coronary intervention, but choosing the optimal treatment duration and composition has become a major challenge. Numerous studies have shown that certain patients benefit from either shortened or extended treatment duration. Furthermore, trials evaluating novel antithrombotic strategies, such as P2Y12 inhibitor monotherapy, low-dose factor Xa inhibitors on top of antiplatelet therapy, and platelet function- or genotype-guided (de-)escalation of treatment, have shown promising results. Current guidelines recommend risk stratification for tailoring treatment duration and composition. Although several risk stratification methods evaluating ischaemic and bleeding risk are available to clinicians, such as the use of risk scores, platelet function testing, and genotyping, risk stratification has not been broadly adopted in clinical practice. Multiple risk scores have been developed to determine the optimal treatment duration, but external validation studies have yielded conflicting results in terms of calibration and discrimination and there is limited evidence that their adoption improves clinical outcomes. Likewise, platelet function testing and genotyping can provide useful prognostic insights, but trials evaluating treatment strategies guided by these stratification methods have produced mixed results. This review critically appraises the currently available antithrombotic strategies and provides a viewpoint on the use of different risk stratification methods alongside clinical judgement in current clinical practice. Graphical Abstract: